Penyelenggaraan Pendidikan Agama Alternatif: Studi Kasus pada SMP Al-Hikmah Surabaya - Djuhardi AS (Badan Litbang dan Diklat Kementerian Agama RI, 2011)
AbstractAn alternative religious education is a learning institution that has the advantages of entrenched religious values and teachings in response to the existing religious education systems believed to have met none but less public expectations. Its appearance hence can be caused by cultural, social and spiritual factors. Whatever is offered to the community, the religious education should basically serve to provide learnenrs with divine worth in addition to knowledge and skills, democratic values and so on. An alternative model of religious education for the community, thus, find its significance in the context of cultural initiatives they carry out in response to the one failing to perform as expected. The AL-Hikmah Junior is selected for sampleng for it has its own peculiarities and leads viewed from such aspects as institution, vision and mission, management, as well as facilities and infrastucture in addition to its different cultural environment from that of other existing mainstream educational institutions in the same region.Â AbstrakPendidikan agama alternatif merupakan lembaga pendidikan yang memiliki keunggulan dalam penanaman nilai-nilai dan ajaran agama sebagai respon terhadap sistem pendidikan agama yang ada karena dianggap belum memenuhi harapan masyarakat. Munculnya pendidikan agama alternatif dapat disebabkan faktor kultural, sosial amupun keagamaan. Apapun yang ditawarkan pada msyarakat, pada dasarnya pendidikan agama harus berfungsi untuk memberikan peserta didik dengan nilai-nilai ilahiyah, pengetahuan dan keterampilan, nilai-nilai demokrasi dan sebagainya. Jadi model pendidikan agama alternatif bagi masyarakat menemukan signifikansinya dalam konteks inisiatif kultural yang dilakukan masyarakat sebagai respon terhadap model pendidikan yang tak memenuhi harapan. Pemilihan Sekolah Menengah Pertama (SMP) AL-Hikmah karena lembaga pendidikan ini memiliki kekhususan dan keunggulan tersendiri, baik dari kelembagaan, visi dan misi, manajemen, sarana dan prasarana yang dibangun serta lingkungan budaya sekolah yang berbeda dengan lembaga pendidikan mainstream yang ada dimana SMP AL-Hikmah berada.